2013
DOI: 10.4236/crcm.2013.25082
|View full text |Cite
|
Sign up to set email alerts
|

A case of kidney metastasis in vulvar squamous cell carcinoma: A case report and review of literature

Abstract: Vulvar cancer is an uncommon tumor and represents 3%-5% of all female genital tract malignancies. Squamous cell carcinoma (SCC) is the most common carcinoma of the vulva. Distant metastasis of recurrent vulvar squamous cell carcinoma is rare and occurs late in the disease process. We report the first case of kidney metastasis from a vulvar squamous cell carcinoma in a 68-year-old Caucasian female. On initial presentation she was treated with radical vulvectomy, upper urethrectomy with bilateral inguinal and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…With only having one reported case in the literature to date, renal metastases from vulvar SCC can be considered extremely rare. In the first case that was reported, the patient had a 24-month recurrence-free survival time after radical surgery and chemo-radiation of vulvar cancer relapse ( 3 ). She was treated with radical vulvectomy and chemo-radiation therapy due to vulvar SCC and remained in remission for 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With only having one reported case in the literature to date, renal metastases from vulvar SCC can be considered extremely rare. In the first case that was reported, the patient had a 24-month recurrence-free survival time after radical surgery and chemo-radiation of vulvar cancer relapse ( 3 ). She was treated with radical vulvectomy and chemo-radiation therapy due to vulvar SCC and remained in remission for 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…Distant metastases of vulvar SCC most commonly involve the lung, liver, bone, skin, and lymph nodes. Metastasis from vulvar SCC to the kidneys is extremely rare, with only one case reported in the literature to date ( 3 ). In this report, we shall discuss a rare case of renal metastasis from a primary vulvar SCC.…”
Section: Introductionmentioning
confidence: 99%
“…Older women are more likely to have HPV-negative disease and there is an association with vulvar lichen sclerosus [2] . Although metastization is rare with haematogenous dissemination to distant sites occurring in only 8–12% of patients [3] , the most common sites for metastasis are the lung, bone, liver and lymph nodes [4] . When metastization occurs, there is usually a low response to surgery/radiotherapy, with a 5-year survival rate of less than 5% [5] .…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that for HPV16-positive VSCC, the virus was included in cell spread from the original tumor site and was even detected in lesions far away from primary site. Distant spread in vulvar carcinoma is unusual [37] but in a few published case reports cardiac [38] , kidney [39] , liver and lung metastasis [40] are reported.…”
Section: Discussionmentioning
confidence: 99%